2003
DOI: 10.1046/j.1523-1755.2003.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal induces apoptosis through activation of p38 mitogen-activated protein kinase in rat mesangial cells

Abstract: These results suggest a potential role for MG in glomerular injury through p38 MAPK activation under diabetic conditions and may serve as a novel insight into the therapeutic strategies for diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 60 publications
9
85
0
1
Order By: Relevance
“…Renal p38 in experimental diabetes R Komers et al lation of products of glycation reactions, and oxidative stress, have been shown to induce p38 signaling in mesangial cells, podocytes and in proximal tubular cells in vitro. 3,16,[23][24][25] In agreement with these findings, present studies, conducted in more clinically relevant settings, show that poor metabolic control is the major determinant of p38 activity in the diabetic kidney. Our findings are also in agreement with limited in vivo evidence in the setting of Type 1 diabetes, suggesting increased expression of P-p38 protein expression in wholekidney homogenates harvested from mice early after induction of STZ-diabetes.…”
Section: Renal P38 In Experimental Diabetessupporting
confidence: 90%
See 1 more Smart Citation
“…Renal p38 in experimental diabetes R Komers et al lation of products of glycation reactions, and oxidative stress, have been shown to induce p38 signaling in mesangial cells, podocytes and in proximal tubular cells in vitro. 3,16,[23][24][25] In agreement with these findings, present studies, conducted in more clinically relevant settings, show that poor metabolic control is the major determinant of p38 activity in the diabetic kidney. Our findings are also in agreement with limited in vivo evidence in the setting of Type 1 diabetes, suggesting increased expression of P-p38 protein expression in wholekidney homogenates harvested from mice early after induction of STZ-diabetes.…”
Section: Renal P38 In Experimental Diabetessupporting
confidence: 90%
“…These mechanisms could include deleterious effects such as activation of the renin-angiotensin system, 14,23,37 oxidative stress, 37 extracellular matrix (ECM) production and cellular hypertrophy, 2 induction of growth cytokines, 2,3 mesangial and podocyte apoptosis, 16,24 and glucose-induced 12-lipooxygenase pathway signaling, 22 as well as possibly protective effects. such as cytoskeleton reorganization in podocytes that temporarily prevents the development of albuminuria.…”
Section: Renal P38 In Experimental Diabetesmentioning
confidence: 99%
“…19,[22][23][24] The absence of these effects in our study suggests that these diabetic factors induce their cellular effects independently of their ability to modify collagen IV.…”
mentioning
confidence: 55%
“…One of the primary signalling pathways through which apoptosis is induced is the MAP kinase pathway. It has been shown that advanced glycation endproducts induce apoptosis in Schwann and mesangial cells partly through p38 map kinase signalling (28,43). Another member of the MAP kinase family, JNK, has been shown to mediate apoptosis of other mediators including TNF-α (29,48).…”
Section: Resultsmentioning
confidence: 99%